2015
DOI: 10.1371/journal.pone.0144755
|View full text |Cite
|
Sign up to set email alerts
|

Serum Insulin-Like Growth Factor-1 in Patients with De Novo, Drug Naïve Parkinson’s Disease: A Meta-Analysis

Abstract: ObjectiveInsulin-like growth factor-1 (IGF-1) is reported to be neuroprotective in the setting of Parkinson’s disease (PD), and there is increasing interest in the possible association of serum IGF-1 levels with PD patients, but with conflicting results. Therefore, we conducted a meta-analysis to evaluate the association of serum IGF-1 levels in de novo, drug naïve PD patients compared with healthy controls.MethodsPubmed, ISI Web of Science, OVID, EMBASE, and Cochrane library databases from 1966 to October 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 25 publications
1
12
1
Order By: Relevance
“…These IGF-1 concentrations inversely correlate with the UPDRS-III score (i.e. with motor function), verbal episodic memory, visuoperceptual abilities and attention/ executive functions; been not found such correlation on healthy subjects [171][172][173][174][175][176][177][178][179][180][181]. As it has been shown, lower IGF-1 levels at the beginning of PD are associated with a worse disease progression and prognosis.…”
Section: Theoretical Relationship Between Parkinson's Disease and Igfmentioning
confidence: 86%
See 2 more Smart Citations
“…These IGF-1 concentrations inversely correlate with the UPDRS-III score (i.e. with motor function), verbal episodic memory, visuoperceptual abilities and attention/ executive functions; been not found such correlation on healthy subjects [171][172][173][174][175][176][177][178][179][180][181]. As it has been shown, lower IGF-1 levels at the beginning of PD are associated with a worse disease progression and prognosis.…”
Section: Theoretical Relationship Between Parkinson's Disease and Igfmentioning
confidence: 86%
“…These data could act as a compensatory mechanism due to the lack of IGF-1 signaling feedback and, also, it could be an endogenous protective factor released in response to cell death and oxidative damage promoted by the disease itself. Such hypothesis is further sustained by a progressive PD model study where IGF-1 was found to protect the nigrostriatal pathway, and that this protection was preceded by activations of key pro-survival signaling cascades, such as Akt [181,196].…”
Section: Theoretical Relationship Between Parkinson's Disease and Igfmentioning
confidence: 96%
See 1 more Smart Citation
“…We also found a positive correlation of serum IGF‐1 with lower striatal SBR for DAT and the FAB scores in PD patients, suggesting that age‐related decreases in IGF‐1 levels may influence cognitive function in PD‐related disorders, interacting with the degeneration of nigrostriatal dopaminergic neurons. De novo and untreated patients with PD showed higher IGF‐1 levels than healthy controls, and serum IGF‐1 levels in PD patients negatively correlated with disease duration . Numao et al showed that MSA patients had higher serum IGF‐1 levels than controls, but there was no difference in serum IGF‐1 levels between PD patients and controls.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated high levels of serum IGF-1 in PD patients compared with controls. A meta-analysis by Li et al [24](166 PD patients and 323 healthy controls) demonstrated high levels of serum IGF-1 in PD patients compared with controls. Godau et al [7] conducted a study on 139 healthy controls and 15 PD patients found significant high serum IGF-1 in PD (P =0.004).…”
Section: Discussion:-mentioning
confidence: 99%